(untitled) (Heritage, 2023)
"Travel through biography" is a work that, by its very title, represents a challenge for readers and researchers. The phrase from the title, which contains two genre determinants – travel writing and biography (the truth is, both have inseparability from the personality of the author) opens up the problem of the formal code in which the work will be interpreted. That is why we decided to look at this work from a structural-semiotic point of view and thus determine the basic mechanisms of the structure of the text from which the work was created, i.e. the poetic principles that make it a coherent literary structure, bearing in mind first of all the procedures of description, essayization, narration, fragmetization and assembly. From the aspect of linguistic stylistics, Kapor is used in the realization of those procedures, which are, above all, lexical (reprise, synonym, deictic) and stylistic (anaphors, epiboles, epiphores, iterations) connectors as signals of the contextual inclusion of the sentence. The dialectic of the external, apostrophized by the travelogue genre, and the internal, represented by the biography genre, leads to the conclusion that the work represents an intimate identity topography of places stored in the memory of the being inscribed in the text.